Effectiveness of Hard Versus Soft Occlusal Splints in the Management of Patients with Temporomandibular Disorders: A Systematic Review - Dr. Hirenkumar Rana; Dr. Shruti Mehta; Dr. Chandrasinh Rajput; Dr. Priyanka Sutariya (Innovative Journal of Medical and Health Sciences, 2021)
Abstract Introduction: Temporomandibular disorders (TMDs) are the most common non-dental orofacial pain that has a major impact on the quality of life. Management of TMD can be either conservative or surgical treatments. Occlusal splint therapy is chosen for the treatment of dysfunctions as it is relatively simple, reversible, non-invasive, and costs less than other treatments. Hard splints are fabricated from self or heat cured acrylic resin, forming a hard and rigid occlusal surface while the soft or resilient splints forming a somewhat flexible occlusal surface that can be easily adjusted to an adequate contact pattern. Objectives: With continuous debate and lack of consensus regarding which are more effective in the management of the TMD, soft or hard occlusal splint, this paper presentation attempts to review the current literature regarding the effectiveness of hard v/s soft occlusal splints in patients with TMDs. Methods: PubMed, Cochrane CENTRAL databases, Google Scholar, Embase, and Google searches were performed using the PICO strategy. Randomized Controlled Trials (RCTs) which compared hard versus soft occlusal splint were the only articles to be included. Titles and abstracts were screened, data extracted and articles were assessed for risk of bias and quality of reporting. A thorough systematic review was performed for relevant RCTs. Results: Six out of 2708 articles were selected based on the defined criteria set for the review. Four articles suggested the patients improved over time and both the hard and soft splints offered the benefit equally. One report suggested hard splint to be superior, while another suggested soft splint to be more effective. Conclusion: Both hard and soft occlusal splints proved to be effective in patients with TMDs. The scarcity of current external evidence emphasizes the need for more clinical research. Keywords: Myofascial Pain, Temporomandibular Disorders, Hard Occlusal Splint, Soft Occlusal Splint, Systematic Review.